Supporting unified distributed management and autonomic decisions: design, implementation and deployment - Ferreira, Carlos (2019)
Submitted by VELEZ (fjv@ubi.pt) on 2019-08-28T10:40:10Z No. of bitstreams: 1 R20_J_Netwrk_Syste_Manag.pdf: 3591851 bytes, checksum: f3d504a6806c73135fa9c5330bf415a8 (MD5)